Advances in parasitology. Vol. 63 - Baker, John R. (John Robin); Muller, Ralph, 1933-; Rollinson, D.; ScienceDirect eBooks (Amsterdam : Academic Press, 2006)
First published in 1963, Advances in Parasitology contains comprehensive and up-to-date reviews in all areas of interest in contemporary parasitology. Advances in Parasitology includes medical studies on parasites of major influence, such as Plasmodium falciparum and Trypanosomes. The series also contains reviews of more traditional areas, such as zoology, taxonomy, and life history, which shape current thinking and applications. Eclectic volumes are supplemented by thematic volumes on various topics including "Remote Sensing and Geographical Information Systems in Epidemiology" and "The Evolu.
The Family ParamphistomidaeOther Families of Interest; Concluding Remarks; Acknowledgments; References; Systematics and Epidemiology of Trichinella; Introduction; Advances in the Systematics of Trichinella; The Taxonomy of the Genus; Phylogeny; Biogeography; Epidemiology; A New Approach: Trichinella-Free Areas or Farms. is it Possible?; Concluding Remarks; Acknowledgements; References; Index.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Parasitology; MEDICAL -- Parasitology; Parasitology; Electronic books